2019
DOI: 10.1103/physrevb.99.155144
|View full text |Cite
|
Sign up to set email alerts
|

Charge order inβ-phase BEDT-TTF salts

Abstract: Experimentally we establish the quantitative phase diagram of 1/4-filled β ′′ -(BEDT-TTF)2SF5RSO3 with a tendency towards charge order. Comprehensive optical, transport and susceptibility measurements reveal the insulating nature and magnetic properties of the chargeordered ground state. Going from R =CHF via CH2CF2 and CHFCF2 towards CH2, a finite charge disproportionation appears and grows up to 2δ = 0.5e, as evidenced by charge-sensitive molecular vibrations. This is accompanied by an increase of electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
(67 reference statements)
3
18
1
Order By: Relevance
“…It is clearly found that the parameters of the two salts fall in the correlation derived from our results. Quite recently, optical measurements [14,15] point out that the superconductivity found in β ′′ -(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 also coexists with the charge order similar to the present case. These facts suggest that the β ′′ -type organics can be universally discussed in a generic phase diagram with the electron correlation like Fig.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…It is clearly found that the parameters of the two salts fall in the correlation derived from our results. Quite recently, optical measurements [14,15] point out that the superconductivity found in β ′′ -(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 also coexists with the charge order similar to the present case. These facts suggest that the β ′′ -type organics can be universally discussed in a generic phase diagram with the electron correlation like Fig.…”
supporting
confidence: 77%
“…As is shown in Fig. 1(a), the universal phase diagram of the β ′′ -type salts proposed in the earlier works [11][12][13][14][15] claims that the superconducting phase is adjacent to the charge ordered (CO) phase caused by intersite Coulomb repulsion V . It implies that the CO phase appears as an underlying phase for the emerging superconductive phase.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…To that end, we measured the out-of-plane (E c) optical conductivity in the low-temperature insulating state of β ′′ -I and β ′′ -MI and compare it in Fig. 2 to β ′′ -SC and β ′′ -M 14,17 . The ν 27 (B 1u ) vibration around 1460 cm −1 is known to be most sensitive to the charge on the molecule and is therefore commonly utilized as a local probe 22,23 .…”
Section: A Charge Disorportionation As Order Parametermentioning
confidence: 99%
“…(b) A generic phase diagram of 1/4-filled two-dimensional electron systems suggests 8 that the superconducting state is located right at the boundary of chargeordered insulator and Fermi-liquid metal. We show the position of β ′′ -SC and its fully-deuterated analogue β ′′ -d8SC, as well as β ′′ -(BEDT-TTF)2SF5RSO3 with slightly modified anions R = CH2, CHFCF2 and CHF, called β ′′ -I, β ′′ -MI and β ′′ -M, respectively 14 . The upper horizontal scale indicates the charge disproportionation 2δ determined in this work.…”
Section: Introductionmentioning
confidence: 99%